Primary pancreatic hydatid cyst: a case report and literature review - Wu, Yilei (BMC Gastroenterol, 2021)
BACKGROUND: Hydatid cysts are parasitic zoonoses that often occur in the liver. Pancreatic hydatid cysts are very rare and are usually misdiagnosed as pancreatic cystadenomas. At present, surgical resection combined with albendazole administration is the standard treatment for pancreatic hydatid cysts. However, making accurate preoperative diagnoses and avoiding intraoperative cystic rupture are challenges for surgeons. CASE PRESENTATION: A 28-year-old woman from the pastoral area presented to the surgical office complaining of abdominal pain and new-onset jaundice that began 9 days earlier. An enhanced computed tomography scan demonstrated a 6.0 × 5.3 cm pancreatic head cystic mass that compressed the common bile duct and induced choledochectasia. The preoperative diagnosis was pancreatic head cystadenoma, and laparotomic pancreaticoduodenectomy was initiated successfully. The intra- and postoperative diagnosis was pancreatic hydatid cyst. The patient was discharged uneventfully 7 days after the operation. A 1-year course of albendazole (15 mg/kg/day) was admitted. CONCLUSION: Pancreatic hydatid cysts are rare and often misdiagnosed as other types of cysts. History of living in an area in which the causative organism is endemic and positive anti-echinococcus IgG antibody status could help with the diagnosis. Radical resection combined with oral albendazole administration is the standard treatment for pancreatic hydatid cysts. Avoiding perioperative cystic rupture and abdominal echinococcosis implantation metastasis is crucial for the success of the operation.